Spatial mismatch, wages and unemployment in metropolitan areas in Brazil - Ana Maria Bonomi Barufi; Eduardo Amaral Haddad (REGION, 2017)
The spatial mismatch hypothesis states that a lack of connection to job opportunities may affect an individual's prospects in the labour market, especially for low-skilled workers. This phenomenon is especially observed in large urban areas, in which low-skilled minorities tend to live far away from jobs and face geographical barriers to finding and keeping jobs. This paper aims to investigate whether this negative relationship between spatial mismatch and labour market outcomes is valid in Brazil after controlling for individual characteristics. Our conclusions indicate that there is no clear relation between different measures of accessibility to jobs and the probability of being unemployed. However, for wages there is a clear correlation, which is stronger in larger metropolitan areas in the country. Given the exploratory nature of this work, our results still rely on strong identification hypotheses to avoid potential bias related to simultaneous location decisions of workers and firms within the city. Even if these conditions do not hold, the results are still meaningful as they provide a better understanding of the conditional distribution of wages and the unemployment rate in the biggest metropolitan areas of Brazil.
Keywords: 330; Spatial Mismatch; Labour Market; Metropolitan Areas